Using an expanded Theory of Planned Behavior to predict adolescents' intention to engage in healthy eating. Issue 1 (1st January 2016) - Chan, Kara; Prendergast, Gerard; Ng, Yu-Leung
ABSTRACT: A study was conducted to test an expanded Theory of Planned Behavior (TPB) in predicting healthy eating intention among adolescent boys and girls in mainland China. Two variables (perceived barriers and self-efficacy) were added to the TPB. A purposive sampling design was adopted to select schools, then students. Altogether, 635 adolescents were asked to complete a structured questionnaire about healthy eating. Results of confirmatory factor analysis and structural equation modeling supported the structural validity of the proposed expanded model. Confirmatory factor analysis suggested that selected items of the perceived behavioral control and perceived barriers should be combined to form a new measure of perceived behavioral control. The new measure of perceived behavioral control and self-efficacy was found to be more influential than attitude as well as subjective norm in predicting healthy eating. Past behavior and gender were found to be significant moderating variables.